2010
DOI: 10.1186/1471-2474-11-3
|View full text |Cite
|
Sign up to set email alerts
|

Modular titanium alloy neck adapter failures in hip replacement - failure mode analysis and influence of implant material

Abstract: BackgroundModular neck adapters for hip arthroplasty stems allow the surgeon to modify CCD angle, offset and femoral anteversion intraoperatively. Fretting or crevice corrosion may lead to failure of such a modular device due to high loads or surface contamination inside the modular coupling. Unfortunately we have experienced such a failure of implants and now report our clinical experience with the failures in order to advance orthopaedic material research and joint replacement surgery.The failed neck adapter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
152
1
19

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(181 citation statements)
references
References 23 publications
6
152
1
19
Order By: Relevance
“…Chemomechanical stress is reported to be higher in titanium modular necks compared with cobalt-chromium bimodular necks. This also is true in femoral stems used for primary THA compared with stems used in revisions owing to the longer and larger anchorage cones of revision stems [7,9,11,16,33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chemomechanical stress is reported to be higher in titanium modular necks compared with cobalt-chromium bimodular necks. This also is true in femoral stems used for primary THA compared with stems used in revisions owing to the longer and larger anchorage cones of revision stems [7,9,11,16,33].…”
Section: Discussionmentioning
confidence: 99%
“…Because of a substantial rate of loosening by subsidence with the bimodular PROFEMUR 1 E, in 2006 the bimodular PROFEMUR 1 Z stem was chosen for use. Because of reports of fracture of the bimodular neck, use of PROFEMUR 1 stems that accommodated the bimodular neck was abandoned [5,7,13,16,28,32,33]. Bearing surface…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Large-diameter femoral heads and trunnion geometry were common features identified in the studies that associated elements of implant design with tribocorrosion in taper junctions [7,18,19,32]. Larger head sizes increase torsional forces at the trunnion [9], and this may be a contributing factor in the increased failure rates seen metalon-metal (MoM) THAs [17,22], which have a high revision rate of 19% after 12 years [2].…”
Section: What Clinical Problems Have Been Reported In Patients With Mmentioning
confidence: 99%
“…The interaction terms were based on time intervals of zero to two, two to four, four to six, and six to eight years. A test of the interaction terms was nonsignificant (x 2 [3] = 0.84, p = 0.84); therefore, these terms were removed. The iterated model indicated that the overall head size effect was nonsignificant, with the point estimate favoring a harmful effect of small-head-size C-C implants (b = 0.097, SE = 0.221).…”
Section: Comparison Of >28-mm C-c and All M-hxlpe Bearingsmentioning
confidence: 99%